A Rationalization of the Weak Axiom of Revealed Preference - Victor H. Aguiar; Per Hjertstrand; Roberto Serrano (Research Institute of Industrial Economics (IFN), 2020)
We offer a rationalization of the weak axiom of revealed preference (WARP) and of the weak generalized axiom of revealed preference (WGARP) for both finite and infinite data sets of consumer choice. We call it maximin rationalization, in which each pairwise choice is associated with a local utility function. We develop its associated revealed-preference theory. We show that preference recoverability and welfare analysis à la Varian (1982) may not be informative enough when the weak axiom holds but when consumers are not utility maximizers. In addition, we show that counterfactual analysis may fail with WGARP/WARP. We clarify the reasons for these failures and provide new informative bounds for the consumer's true preferences, as well as a new way to perform counterfactual analysis. Finally, by adding the Gorman form and quasilinearity restrictions to the "local" utility functions, we obtain new characterizations of the choices of the Shafer (1974) nontransitive consumer and those choices satisfying the law of demand.
Keywords: C60; D10; 330; Consumer choice; Revealed preference; Maximin rationalization; Nonconvex preferences; Reference-dependent utility; Law of demand